Анализ методов расчета магнитного поля пространственного контура с током - Геляровская, Оксана Анатольевна; Лупиков, Валерий Сергеевич (НТУ "ХПИ", 2010)
Приведены данные численного моделирования внешнего магнитного поля пространственного контура с током. Получены оценки величины поля для двух вариантов разбивки этого контура на простые контуры в соответствии с методом магнитных моментов, плоскости которых отличаются. Результаты исследований рекомендуется учитывать при использовании метода магнитных моментов для анализа магнитного поля контуров с токами, которые имеют сложную пространственную конфигурацию.

Numerical modeling of an external magnetic field in the spatial contour with a current are resulted. Estimations of the field for two variants of the contour breakdown according to the magnetic moments method on simple contours with different planes are received. The researches results are recommended to be considered at use of the magnetic moments method for the magnetic field analysis in contours with currents which have a complicated spatial configuration.
Analysis of methods used for computation of magnetic fields in the spatial contour with current
Keywords: пространственный контур; внешнее магнитное поле; метод моментов; численное моделирование; spatial contour; external magnetic field; magnetic moments method; numerical modeling